Pushing Boundaries in Southwestern Archaeology : Chronometry, Collections, and Contexts - Baxter, Erin; Nash, Stephen E. (Stephen Edward), 1964- (Book collections on Project MUSE., 2022)
"Pushing Boundaries in Southwestern Archaeology draws together proceedings from the sixteenth biennial Southwest Symposium to explore the 2018 theme of "pushing boundaries," with topics ranging from Bears Ears National Monument to big data in pre-Columbian history to the potential of collections, to permeable boundaries in Plains-Pueblo interactions"--